The Transformations of the Writing Body: Rhetoric, Monumental Art, and Poetry in Ovid's Metamorphoses. - Kirichenko, Alexander (Symbolae Osloenses, 2021)
This article analyses the power dynamics that Ovid stages in the Metamorphoses as interplay of rhetoric, monumental art, and poetry. It argues that (1) the transformations of gods can be read as a metaphor of rhetoric subjecting the audience to the speaker's will; (2) that the products of the transformations of humans can be regarded as notional monuments to divine power; (3) that, for Ovid, all successful ideological constructs are based on a similar combination of rhetorical manipulation and "monumentalization"; (4) that, at the same time, Ovid casts metamorphosis as a product of the ability of the human imagination to recognize a human presence behind every non-human object, including the "monuments" constructed by superhuman powers; (5) that Ovid conceives of the "re-humanizing" effect of poetry as a function of its ability to make the audience recognize themselves in it; and (6) that the immortality that Ovid attributes to his own text is a function of his writing producing a similar effect on the readers.